1975
DOI: 10.1007/bf02532350
|View full text |Cite
|
Sign up to set email alerts
|

Brassica campestris var. Span: I. Fractionation of Rapeseed oil by molecular distillation and adsorption chromatography

Abstract: Procedures for the large scale isolation of pure triglycerides and fractions rich in nontriglyceride components from Span rapeseed oil are described. Fractionation of Brassica campestris var. Span rapeseed oil by molecular distillation yielded 4 triglyceride fractions, all of which contained traces of sterol esters. An additional triglyceride fraction rich in free and esterified sterols and other volatile components was obtained from the oil. Separation by adsorption chromatography of Span rapeseed oil yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The differences observed in lesion response (Tables IV and V) when the three erucic acid containing diets were fed to male rats might be explained by the following possibilities: (a) The pigs, from which the RPF was prepared, may have removed some cardiotoxic component from RSO, toxic to male rats (5), but not to pigs (7)(8)(9). However, in a previous attempt (21) to reduce Span RSO toxicity by subjecting the oil to exhaustive molecular distillation or adsorption chromatography, we were unable to demonstrate either the presence of a distillable toxic component or show that the highly purified triglycerides were less cardiotoxic than the original oil (13). (b) Triglycerides of rapeseed oil differ from triglycerides of pig adipose tissue in fatty acid composition (Table I) and positional distribution of fatty acids on the glycerol moiety (Hulan et al, unpublished data).…”
Section: As Indicated Inmentioning
confidence: 88%
“…The differences observed in lesion response (Tables IV and V) when the three erucic acid containing diets were fed to male rats might be explained by the following possibilities: (a) The pigs, from which the RPF was prepared, may have removed some cardiotoxic component from RSO, toxic to male rats (5), but not to pigs (7)(8)(9). However, in a previous attempt (21) to reduce Span RSO toxicity by subjecting the oil to exhaustive molecular distillation or adsorption chromatography, we were unable to demonstrate either the presence of a distillable toxic component or show that the highly purified triglycerides were less cardiotoxic than the original oil (13). (b) Triglycerides of rapeseed oil differ from triglycerides of pig adipose tissue in fatty acid composition (Table I) and positional distribution of fatty acids on the glycerol moiety (Hulan et al, unpublished data).…”
Section: As Indicated Inmentioning
confidence: 88%
“…Although free phytosterols can be distilled with reasonable ef ciency, approximately half of corn oil phytosterols are long-chain fatty acid esters with volatility very similar to triglycerides, making removal impossible unless multiple distillations are performed in instruments with high resolving power. 16,17 In a second experiment, removal of phytosterols was attempted by a different technique. Corn oil was saponi ed, the fatty acids were precipitated with barium, the sterols were extracted four times with dichloroethane, and the fatty acids were then re-esteri ed to glycerol.…”
Section: The Fatty Acid Hypothesismentioning
confidence: 99%
“…29 Molecular distillation results in incomplete removal of sterol esters as noted above and requires temperatures in excess of 225°C, which are likely to damage polyunsaturated fatty acids. 16,17 At rst glance, saponi cation of an oil followed by isolation of puri ed fatty acids and resynthesis of the triglyceride would seem to be very helpful because such methods are used to prepare oils with de ned fatty acid composition. But this process does not obviate the need to remove phytosterols by a dedicated separate step.…”
Section: The Fatty Acid Hypothesismentioning
confidence: 99%
“…The increased incidence of lesions in this strain of rat has been attributed to cardiotoxic contaminants (3,4), residual erucic (A13-cis-docosenoic) acid (22:1) (5), or a fatty acid imbalance (2,6-9) of LEAR oils. We considered the possibility of cardiotoxic contaminants in LEAR oils and, therefore, fractionated Span rapeseed oil (RSO) containing 4.8% 22:1 by molecular distillation and adsorption chromatography to prepare pure triglycerides and fractions enriched in nontriglyceride components (10). The results of feeding these fractions to rats suggested that the cardiopathogenic properties of Span RSO were associated with the triglycerides of the oil, and not with nontriglyceride contaminants present in the fully refined oil (8).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean oil was similarly fractionated by molecular distillation to evaluate possible effects of the molecular distillation procedure itself. To increase the purity of the triglycerides of the LEAR oil, the purest triglyceride fraction from molecular distillation was further purified by column chromatography, instead of using the two methods independently as performed previously (10). Finally, a protocol was set up to conduct the feeding trial in two independent laboratories (Agriculture; Canada, Ottawa and Department of Veterinary Pathology, University of Saskatchewan) with an exchange of histological sections of myocardium before decoding and evaluation of the data.…”
Section: Introductionmentioning
confidence: 99%